Recovery of the soil fungal microbiome after steam disinfection to manage the plant pathogen Fusarium solani - Larson, Eric R.; Crandall, Sharifa G. (Frontiers in Plant Science, 2023)
Soil disinfection using high temperatures via steam is a promising approach to manage plant pathogens, pests, and weeds. Soil steaming is a viable option for growers who are moving away from dependence on chemical soil fumigants, especially in plant nursery or high tunnel environments. However, there are few studies that investigate how soil steaming causes substantial disturbance to the soil by killing both target pathogens and other soil biota. Steaming treatments also change the trajectory of the soil microbiome as it reassembles over time. Growers are interested in the health of soils after using steam-disinfection, especially if a virulent pathogen colonizes the soil and then flourishes in a situation where there are very few microbes to suppress its growth. Should recruitment of a virulent pathogen occur in the soil, this could have devasting effects on seed germination, seedling establishment and survival. Beneficial microbes are often used to prevent the colonization of plant pathogens, especially after a soil-steaming event. Here, we experimentally test how soil fungal communities assemble after steaming disinfection. We introduce to steam-treated soil Fusarium solani, an important fungal pathogen of soybean and Trichoderma harzianum, a known beneficial fungus used for soilborne pathogen suppression. Results show that F. solani significantly affects the relative abundance and diversity of the soil fungal microbiome, however, T. harzianum does not mitigate the amount of F. solani in the steam treated soil. Within the T. harzianum microbial addition, the soil fungal communities were similar to the control (steaming only). This result suggests inoculating the soil with T. harzianum does not drastically alter the assembly trajectory of the soil fungal microbiome. Other soil amendments such as a combination of Trichoderma spp. or other genera could suppress F. solani growth and shift soil microbiome composition and function post-steaming, however, more experimental research is needed.